Development and optimization of lattice structure on the walnut shell reinforced PLA composite for the tensile strength and dimensional error properties. (November 2022) - Palaniyappan, Sabarinathan; Veeman, Dhinakaran; Sivakumar, Narain Kumar; Natrayan, L.
Abstract: The organic fillers and honeycomb lattice structure intruded novel bio-composite materials for the 3D printing application is a practical and eco-friendly approach for developing lightweight biopolymeric components. The present work investigates the impact of incorporation of hexagon lattice structure on the walnut shell/PLA polymeric composite material using the Fused Deposition Modelling method. The printing process parameters such as nozzle temperature, layer height, infill density, and printing speed are varied to optimize the tensile and dimensional area error properties. Taguchi optimization technique is employed to find the optimal printing condition for the effective experimental output responses. The results from the experiments clearly show that the maximum tensile strength of 2.684 MPa was observed on the optimized printing condition of nozzle temperature of 210℃, a layer height of 0.1 mm, an infill density of 100 %, and a printing speed of 20 mm/ sec . The developed mathematical model from the regression analysis depicted the R-square value concerning the output responses like tensile strength will be 92.24, and dimensional area error will be 87.48. It proclaims that; the model is fit for the large-scale production of the hexagon lattice structure in the walnut shell/PLA composite. Furthermore, the macrographs of the tested composites fabricated at higher infill density exhibited lower sidewall edge failure than the samples fabricated at the lowest infill density percentages.